The effects of segregated education on the social functioning of students with learning disabilities. - Powell, Nicola (My University, 2014)
The purpose of this study was to examine aspects of the social functioning (i . e., peer acceptance, self-concept, loneliness and social alienation) of learning disabled students (n = 58) in the second, third and fourth grades who were in a segregated school. The results were then compared to a study by Vaughn, Elbaum and Schulmrt (1996) which examined the social functioning of second, third and fourth grade learning disabled (LD; n = 16), low achieving (LA; n = 27), and average/high achieving (A/HA; n = 21) students in an integrated school. The results support a model which views social functioning as a composite of interrelated measures. Further, the social functioning of LD Children in the segregated setting was pervasively better than that of the LD as well as LA and A/HA groups. Children in the segregated setting were more accepted by their peers, had a higher academic and general self-concept, and were less alienated than LD children the inclusion setting to whom they were compared. When the LD children in the segregated setting were compared to the LA sample in the integrated school, the LD sample had more positive peer ratings of liking. Finally, when LD children in the segregated setting were compared to A/HA children in the integrated setting, the LD sample were seen to b,e more accepted by the peers and had a more positive global self-worth. Discussiph' foduses on the effects of segregated and integrated education oti/fhe social' functioning of children with LD.